2021
DOI: 10.1371/journal.pone.0259020
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of improvement trends in health workers’ compliance with outpatient malaria case-management guidelines at health facilities with available “test and treat” commodities in Kenya

Abstract: Background Health workers’ compliance with outpatient malaria case-management guidelines has been improving in Africa. This study examined the factors associated with the improvements. Methods Data from 11 national, cross-sectional health facility surveys undertaken from 2010–2016 were analysed. Association between 31 determinants and improvement trends in five outpatient compliance outcomes were examined using interactions between each determinant and time in multilevel logistic regression models and report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…We found that a high proportion of suspected malaria cases were tested in public health facilities compared to private health facilities. A study conducted from Nigeria showed that the testing rate was higher in public health facilities compared to private health facilities because implementing partners were supporting public health facilities with diagnostic supplies and minimal or no support was rendered to private health facilities (9). Our study ndings are surprising given that the National Malaria Control Program (NMCP) subsidized RDTs to be provided through the Joint Medical Stores to scale up and sustain parasite-based diagnosis of malaria in the private sector.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We found that a high proportion of suspected malaria cases were tested in public health facilities compared to private health facilities. A study conducted from Nigeria showed that the testing rate was higher in public health facilities compared to private health facilities because implementing partners were supporting public health facilities with diagnostic supplies and minimal or no support was rendered to private health facilities (9). Our study ndings are surprising given that the National Malaria Control Program (NMCP) subsidized RDTs to be provided through the Joint Medical Stores to scale up and sustain parasite-based diagnosis of malaria in the private sector.…”
Section: Discussionmentioning
confidence: 72%
“…Studies that have been conducted assessed either compliance to either malaria testing or treatment guidelines independently (9,10), yet the success at each step in the cascade in uences the success of the next step. This study assessed the implementation cascade of the malaria Test, Treat, and Track policy to inform strategies to improve compliance to the policy.…”
mentioning
confidence: 99%
“…From this standpoint, the modest decline in quality of care over time might point to the challenge of relying on a volunteer workforce to fill a critical role in the health system. Some prior studies examining integrated management of childhood illness and long-term trends in quality of facility-based care for malaria or other life-threatening paediatric illnesses have documented consistent improvements in quality of care,32 33 though other factors apart from the paid status of these healthcare workers could explain this discrepancy. While iCCM has the potential to increase access to potentially lifesaving care, broader implementation and longer-term reliance on this approach should be accompanied by monitoring and evaluation of quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvements have been described in the management of uncomplicated malaria in Kenya since 2010, with decreasing stock-outs of first line therapeutics and diagnostics and increasing testing rates and compliance with national standard treatment guidelines [25][26][27]. However, there remains a critical gap in the essential drug supply and in-service training for pre-referral malaria casemanagement.…”
Section: Discussionmentioning
confidence: 99%
“…The Kenyan DNMP has undertaken bi-annual national, cross-sectional health facility surveys since 2010 to monitor the implementation of the outpatient 'test and treat' policy described in detail elsewhere [25][26][27]. During each round of the facility surveys, a proportionate, stratified random sample of health facilities was selected from the national master health facility list taking into consideration the facility type, ownership, and administrative boundaries to ensure national representativeness.…”
Section: Data Sourcesmentioning
confidence: 99%